Improving Oral Hygiene Care Using the Singing Method for Mentally Impaired Students Through Teacher and Parent Assistance at SLB Pedagogia Surabaya - Ulfah, Siti Fitria; Agus Marjianto (Frontiers in Community Service and Empowerment, 2023)
Children with intellectual disabilities have a higher risk of dental and oral health problems, this is because they have mental deficiencies and limitations to carry out optimal cleaning of their own teeth. Teachers' knowledge about maintaining oral hygiene for mentally retarded students at SLB BC Optimal Surabaya is in the poor category. Meanwhile, the debris index value measured using the debris index for mentally disabled students is in the bad category, namely 2.17. The latest data update on students' dental health at SLB Pedagogia in 2022 is that mentally disabled students have difficulty in self-development, one of which is how to brush their teeth properly, the majority of students experience bad breath. Oral hygiene care skills for mentally disabled students can be done by involving teacher assistance with innovative methods, namely singing. The singing method can have a fun and memorable impact on mentally retarded students. Practicing oral hygiene care skills for mentally retarded students can be done with the assistance of parents and teachers with the stimulation of singing methods. The results of the community service activities that have been carried out have obtained the following results: oral hygiene care module for students with intellectual disabilities, increased knowledge and skills of teachers and parents regarding correct oral hygiene care, increased oral hygiene care skills for mentally disabled students in SLB Pedagogia in Surabaya City, reduced risk mentally retarded students' bad breath.